The urgency of limiting the presidential term by the constitution in the discourse of extending the term of the President of Indonesia - Sulistyowati; Nadya Maharani, Dewi; Fanani, Ahwan (Dinasti Research, 2023)
The discourse on the extension of the president's term has sparked controversy in society. This paper aims to describe the controversy and analyze it based on the democratic conditions in Indonesia, as well as its connection to the prevailing constitution in Indonesia. The rules governing this issue are found in Article 7 of the 1945 Constitution, which restrictively regulates term limitations. This paper employs a legal study approach with a qualitative research method based on various printed and online document sources.The analysis reveals that the proposal for the extension of the president's term originates from within the government circles and is subsequently supported by party leaders, citing economic development, political stability, and high levels of satisfaction with the government's performance as grounds. However, opposition arises from political parties, legal experts, academics, survey institutions, students, and even the general public. The rejection is based on inconsistencies with the constitution, survey results indicating a desire for a change in national leadership, concerns about power abuse, and non-conducive socio-economic conditions. An unconstitutional extension of the president's term could lead to a regression of democracy in Indonesia. The constitution plays a crucial role as a barrier to preserve the spirit of Reform, ensure the rotation of national leadership, and serve as a hope for national political change. This paper seeks to fill the gap in analyzing the connection between term limitations, democracy, and the constitution in the discourse on extension.